Comparisons of Synchronous and Asynchronous Discussions in an Online Roleplaying Simulation to Teach Middle School Written Argumentation Skills - Riel, Jeremy; Lawless, Kimberly A.; Oren, James B. (Online Learning, 2022)
In this study, different degrees of synchronous and asynchronous online social interactions are investigated in the context of an online educational roleplaying simulation game that is played across multiple classrooms simultaneously to teach argumentation skills and social studies. Results from 45 K–12 middle school social studies teachers and 867 students over 3 study conditions were compared based on the degree of real-time discussion that was embedded in each condition’s version of game (i.e., two scheduled live conferences, one scheduled live conference, and asynchronous-only interactions or zero live conferences). All conditions exhibited significant small to moderate-level pre-post effect sizes, including the condition featuring asynchronous-only discussions. Additionally, the “mid-range” 1 live conference condition exhibited the greatest pre-post effect size in comparison to the other two conditions. This study demonstrates evidence for the benefits of implementing asynchronous-only discussions in digital interventions in comparison to live discussions when synchronous interaction may not be feasible. For designers, implementing both asynchronous and synchronous interactions based on available resources and feasibility can be used to maximize social presence among participants in educational roleplaying games and other virtual learning environments.